MANAJEMEN PEMBELAJARAN KOLABORATIF DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS - Ella Nurlaela; Burhanudin; Rida Susanti; Agus Hariyanto; Nurani; Supyan Sauri (STKIP Subang, 2026)
This study was motivated by the low critical thinking skills of fourth-grade elementary school students during Science and Social Sciences (IPAS) learning activities. Classroom observations indicated that students were generally passive and hesitant to articulate analytical arguments. Therefore, this study aimed to comprehensively analyze the implementation of collaborative learning management—encompassing planning, organizing, actuating, and controlling (POAC)—to enhance students' critical thinking skills. This research employed a qualitative approach using a case study design at SDN Hegarmanah Cikalong, Cianjur. Data were collected through in-depth interviews with the principal, fourth-grade teacher, and students, alongside direct classroom observations and intensive documentation analysis. The findings revealed that: (1) planning was meticulously carried out through the preparation of differentiated lesson modules; (2) organizing involved structuring heterogeneous student groups based on mixed academic proficiencies; (3) actuating was realized via problem-solving sessions, interactive peer discussions, and group presentations; and (4) controlling focused on process-oriented and performance-based assessments. In conclusion, systematic and collaborative learning management successfully fosters a highly interactive, student-centered educational environment that significantly stimulates elementary students' critical thinking competencies.